Nanotechnology and dentistry - Ozak, Sule Tugba; Ozkan, Pelin (European Journal of Dentistry, 2013)
Nanotechnology deals with the physical, chemical, and biological properties of structures and their components at nanoscale dimensions. Nanotechnology is based on the concept of creating functional structures by controlling atoms and molecules on a one-by-one basis. The use of this technology will allow many developments in the health sciences as well as in materials science, biotechnology, electronic and computer technology, aviation, and space exploration. With developments in materials science and biotechnology, nanotechnology is especially anticipated to provide advances in dentistry and innovations in oral health-related diagnostic and therapeutic methods. (Eur J Dent 2013;7:145-151)
Keywords: Nanotechnology; dentistry; nanodentistry; nanocomposite